Performance of p16INK4a ELISA as a primary cervical cancer screening test among a large cohort of HIV-infected women in western Kenya: a 2-year cross-sectional study - Wu, Tara J.; Smith-McCune, Karen; Reuschenbach, Miriam; Knebel Doeberitz, Magnus von; Maloba, May; Huchko, Megan J. (BMJ open, 2016)
Objective A biomarker with increased specificity for cervical dysplasia compared with human papillomavirus (HPV) testing would be an attractive option for cervical cancer screening among HIV-infected women in resource-limited settings. p16INK4a has been explored as a biomarker for screening in general populations. - Design A 2-year cross-sectional study. - Setting 2 large HIV primary care clinics in western Kenya. - Participants 1054 HIV-infected women in western Kenya undergoing cervical cancer screening as part of routine HIV care from October 2010 to November 2012. - Interventions Participants underwent p16INK4a specimen collection and colposcopy. Lesions with unsatisfactory colposcopy or suspicious for cervical intraepithelial neoplasia 2+ (CIN2+; including CIN2/3 or invasive cervical cancer) were biopsied. Following biopsy, disease status was determined by histopathological diagnosis. - Primary and secondary outcome measures We measured the sensitivity, specificity and predictive values of p16INK4a ELISA for CIN2+ detection among HIV-infected women and compared them to the test characteristics of current screening methods used in general as well as HIV-infected populations. - Results Average p16INK4a concentration in cervical samples was 37.4 U/mL. After colposcopically directed biopsy, 127 (12%) women were determined to have CIN2+. Receiver operating characteristic analysis showed an area under the curve of 0.664 for p16INK4a to detect biopsy-proven CIN2+. At a p16INK4a cut-off level of 9 U/mL, sensitivity, specificity, positive and negative predictive values were 89.0%, 22.9%, 13.6% and 93.8%, respectively. The overall p16INK4a positivity at a cut-off level of 9 U/mL was 828 (78.6%) women. There were 325 (30.8%) cases of correct p16INK4a prediction to detect or rule out CIN2+, and 729 (69.2%) cases of incorrect p16INK4a prediction. - Conclusions p16INK4a ELISA did not perform well as a screening test for CIN2+ detection among HIV-infected women due to low specificity. Our study contributes to the ongoing search for a more specific alternative to HPV testing for CIN2+ detection.
Gesehen am 10.09.2021
Der Ausdruck "INK4a" ist im Titel hochgestellt